METHODOLOGIES/STRATEGIES OF MATHS TEACHING FOR DEAF STUDENTS OF ELEMENTARY SCHOOL II (REMUNOM, 2024)
Given the educational and social scenario that the deaf community has been facing over the course of a century, this paper conducts a bibliographical research with the objective of surveying and analyzing the methodologies/strategies that are being used in teaching Mathematics to deaf students in Elementary School II, as well as investigating some active strategies and methodologies, exposing possible alternatives to make the education of these students more meaningful, together with the importance of using the visuospatial space. The objectives emerged in order to seek the answer to the research problem, which is: what are the methodologies/strategies that are being used in teaching Mathematics to deaf students in Elementary School II? This paper also presents a brief retrospective on deafness and the education of the deaf, providing readers with a greater familiarity with the subject and the struggle that this community has been facing over so many years. The research was conducted in the CAPES journals database, considering only academic productions prepared in article format, from 2013 to 2023, with the aim of achieving the proposed objectives. The results of the research also served as a warning, since among 31 articles found, only 2 of them met the objectives set. At the end, these two articles are analyzed and discussed, highlighting the importance of using methodologies/strategies that differ from traditional teaching in the education of these students.